TP53 mutation and immunohistochemical p53 expression characteristics in diffuse large B–cell lymphoma - Jin, Yiping; Wang, Yi; Wang, Lu; Zhang, He; Ren, Beibei; Zheng, Jiawen; Xia, Qingxin; Liu, Yanyan (Frontiers in Oncology, 2025)
Diffuse large B-cell lymphoma (DLBCL) with TP53 mutations has specific clinicopathological features and is usually associated with a poor prognosis. TP53 gene mutations typically lead to aberrant expression patterns of the p53 protein. We studied 123 DLBCL patients at Henan Cancer Hospital, 35.8% (44/123) had TP53 mutations. Analysis of mutation sites in 44 cases of DLBCL patients revealed that the mutations primarily occur in the DNA-binding domain (DBD region) of the encoded p53 protein; among all mutation types, there were 8 truncation or frameshift mutations, and 36 missense mutations. Further, immunohistochemistry (IHC) detected expression levels of p53 protein in 123 DLBCL samples. The mutation results were used as a reference, and receiver operating characteristic (ROC) curve analysis was employed. Ultimately, the expression ratio of 65% and the moderate–strong expression intensity were regarded as the cut–off value, namely high p53 expression or p53 negative (<1%) indicated mutant–type p53 protein. the complete remission (CR) rate of the mutant–type p53 protein group after receiving R–CHOP regimen was 50% (14/28), and the objective response rate (ORR) was 75%, which differed significantly (P<0.01) compared with wild–type p53 protein group [CR rate of 75.86% (66/87) and ORR rate of 89.66%]. Common gene mutations in the mutant–type p53 protein group primarily involve alterations in pathways related to epigenetics, B cell antigen receptor signaling, cell cycle, among others. IHC analysis of the p53 protein is a simple and low-cost approach that can be employed to predict TP53 mutation status and therapy response.